2013
DOI: 10.1016/j.thromres.2013.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Nonsense-mediated mRNA decay was demonstrated in two hypofibrinogenemias caused by heterozygous nonsense mutations of FGG, Shizuoka III and Kanazawa II

Abstract: SummaryWe report two novel hypofibrinogenemias, Shizuoka III and Kanazawa II, which are caused by heterozygous mutations in FGG. Shizuoka III showed c.147delT and 147_149insACA in FGG exon 3 and a subsequent frameshift mutation, resulting in γ23X (stop codon), and Kanazawa II showed c.1205G>A in FGG exon 9, resulting in γ376X.To determine whether the truncated γ-chains, γ23X and γ376X, were synthesized and participated in the assembly of fibrinogen, mutant-type cDNA vectors were transfected into Chinese hamste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…However, we did not observe the shortened length of the -chain for the patient's fibrinogen; therefore, this aberrant -chain may not exist in plasma. These results suggest that aberrant -chain mRNA possessing the premature termination codon at 363 is destroyed in hepatocytes, most likely through nonsense-mediated mRNA decay [16,17]. In addition, the minigene incorporating the IVS-8 deletion partially produced a normal splicing product, but at a lower amount than that of the aberrant product.…”
Section: Discussionmentioning
confidence: 92%
“…However, we did not observe the shortened length of the -chain for the patient's fibrinogen; therefore, this aberrant -chain may not exist in plasma. These results suggest that aberrant -chain mRNA possessing the premature termination codon at 363 is destroyed in hepatocytes, most likely through nonsense-mediated mRNA decay [16,17]. In addition, the minigene incorporating the IVS-8 deletion partially produced a normal splicing product, but at a lower amount than that of the aberrant product.…”
Section: Discussionmentioning
confidence: 92%
“…Genomic DNA was extracted from whole blood cells using a DNA Extraction Kit (WAKO Pure Chemical Ltd., Osaka, Japan), according to the manufacturer’s instructions. In order to amplify all exons and exon–intron boundaries in the Aα-, Bβ-, and γ-chain genes, 32 PCR primers were designed and DNA was amplified by PCR as described elsewhere [ 18 ]. PCR products were purified from agarose gels and directly sequenced using a BigDye TM Terminator Cycle Sequencing Ready Reaction Kit (Thermo Fisher Scientific, Waltham, MA, USA) and 3500 Genetic Analyzer (Life Technologies, Carlsbad, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Our literature review identified a large number of novel mutations accounting for congenital fibrinogen disorders, both quantitative [49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64] and qualitative. [65][66][67][68][69][70][71][72][73][74][75][76] The majority of dysfibrinogenemias, inherited as a dominant trait, are caused by heterozygous missense mutations in one of the three fibrinogen genes.…”
Section: Genetic Diagnosis Of Congenital Fibrinogen Disordersmentioning
confidence: 99%